2019
DOI: 10.4085/1062-6050-113-17
|View full text |Cite
|
Sign up to set email alerts
|

Core-Muscle Training and Neuromuscular Control of the Lower Limb and Trunk

Abstract: Context Comprehensive injury-prevention training (plyometric, agility, balance, and core-stability exercises) has been shown to decrease sport-related injury. The relationship between trunk control and sport-related injury has been emphasized; however, the isolated effects of core-muscle training are unclear. Objective To investigate the effect of a simple 8-week core-muscle–training program on the neuromuscular control of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 29 publications
1
39
1
3
Order By: Relevance
“…Although it is evident the relationship between core control and single limb task control in prepubescent subjects (Hutchinson et al, 2016;Sasaki et al, 2019), only rarely and only recently the specific program effects have been investigated in youth basketball (Sannicandro & Cofano, 2017). The effects of only core stability exercises on jumping performance in young basketball players have recently been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is evident the relationship between core control and single limb task control in prepubescent subjects (Hutchinson et al, 2016;Sasaki et al, 2019), only rarely and only recently the specific program effects have been investigated in youth basketball (Sannicandro & Cofano, 2017). The effects of only core stability exercises on jumping performance in young basketball players have recently been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of Swiss ball and balance pad in our 6-week CSTP was likely to produce positive effect not only in dynamic balance but also trunk endurance including back-extensor endurance. This suggests that the combination of balance and trunk stability exercise would increase the neuromuscular control of the lower extremities as mentioned [37]. These data indicated that 6-week CSTP had a positive impact on subjects' dynamic balance and back-extensor endurance.…”
Section: Effectiveness Of Swiss Ball and Balance Padmentioning
confidence: 59%
“…Thus, the potential of improvement could be greater compared to experienced horse riders. Bagherian et al [34] highlighted that poor-quality mover in dynamic balance task may elicit greater improvement following trunk stability training, because improved trunk stability could enhance the neuromuscular control of the lower limb [37]. Second, biofeedback has been shown to be related to postural control especially when the exercise requires high motion variability, which presents higher trunk translation if visual feedback is eliminated [38].…”
Section: Dynamic Balance Performancementioning
confidence: 99%
“…However, a high hamstring extensibility allows reaching maximal trunk flexion (López-Miñarro, Muyor & Alacid, 2014), which explains the high incidence of pain in the musculoskeletal system of the lower back and knee injuries in dancers (Lampe et al, 2019). It can thus be suggested that, although multi-component prevention programs are the most effective interventions for reducing sport-related injuries (Lauersen, Bertelsen & Andersen, 2014), core strength and stability training as a single factor has demonstrated to improve biomechanics and neuromuscular control, and stability of the lower limbs, reducing on its own the risk of injury in the lower back and lower limbs (De Blaiser et al, 2018;Dello Iacono, Padulo & Ayalon, 2016;Sasaki et al, 2019;Swain & Redding, 2014). In fact, core training program improves core muscles, balance and dance performance in dancers (Watson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%